2017
DOI: 10.1186/s40337-017-0181-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of a family admissions program for adolescents with anorexia nervosa

Abstract: BackgroundThis study investigated patient experience in a Family Admissions Program (FAP) – a pilot treatment program for adolescents with Anorexia Nervosa at the Children’s Hospital, Westmead. Based on Maudsley Family Based Treatment (FBT), the FAP involves an adolescent and his/her family undergoing a two-week family-based hospital admission at the outset of treatment. The program aims to increase intensity and support to a level needed by some families struggling to engage with or access FBT.MethodNarrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Empirical data indicate that the model can be formulated to fit diagnoses, with promising results 10 . FBT for adolescents has been studied across a variety of contexts 1522 and multiple diagnoses 14, 24, 26 with favorable results, underscoring its clinical utility in young patients. Medication trials have led to the FDA approval of lisdexamfetamine for the treatment of BED 48 , and there is promise for olanzapine as an adjunctive treatment for weight gain in AN 4954 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical data indicate that the model can be formulated to fit diagnoses, with promising results 10 . FBT for adolescents has been studied across a variety of contexts 1522 and multiple diagnoses 14, 24, 26 with favorable results, underscoring its clinical utility in young patients. Medication trials have led to the FDA approval of lisdexamfetamine for the treatment of BED 48 , and there is promise for olanzapine as an adjunctive treatment for weight gain in AN 4954 .…”
Section: Resultsmentioning
confidence: 99%
“…Although FBT was originally developed to be delivered in an outpatient setting, recent evidence has supported using the model within treatment programs offered at higher levels of care 1520 . Matthews et al .…”
Section: Psychotherapiesmentioning
confidence: 99%
“…Overall, several participants appreciated that their parents had become more effective caretakers, becoming more supportive, both emotionally and via mutual understanding, and assuming greater responsibility in more supportive ways. A recent study found that a 2-week family admissions program was beneficial in strengthening relationships and providing reunification for the participants (Fink et al, 2017). In line with this, the family-based inpatient approach provides the families with a therapeutic context that both prevents separating significant relationships and offers a new common ground by inviting the family to join forces against the illness.…”
Section: Enabling New Ways Of Understanding and Relatingmentioning
confidence: 91%
“…Outpatient FBT is by no means a one-size fits all treatment (Conti et al, 2017;Fink et al, 2017; Le Grange & Lock, 2014;Murray, Anderson, & Cohn, 2017;Strober, 2014). Augmentations and adaptations are needed to enable a better fit to non-responders and different levels of care (Richards, Subar, Touyz, & Rhodes, 2018).…”
Section: Family-based Inpatient Treatment For Adolescent Anmentioning
confidence: 99%
See 1 more Smart Citation